The type material in the David W. Mitchell myxomycete collection at the Royal Botanic Garden, Kew - Lado, Carlos; Wrigley De Basanta, Diana (Phytotaxa, 2024)
A study of the myxomycete (slime mould) type material in the David W. Mitchell collection, deposited at the K Fungarium of the Royal Botanic Garden Kew, is presented. His collection includes almost 8000 boxes with specimens of myxomycetes, slides, notebooks, and other materials. The search and organisation of the material preserved in Mitchell’s collection, reveal a total of 58 samples of type material (2 holotypes, 29 isotypes, 24 paratypes, 1 isolectotype, 1 syntype, and 1 cultotype). These include type material of 11 taxa authored or co-authored by Mitchell and 42 taxa received as exchange from colleagues. Information and images of the boxes, labels and/or slides of this type material, origin and conservation of the holotypes, and complementary data on these collections, are included. In addition, a list of the publications on myxomycetes of this author and a list of the nomenclatural proposals (new taxa or combinations) published by D.W. Mitchell, are provided.